The lost are the last to die [large type] - Sweazy, Larry D. (Sweazy, Larry D. <U+01C2>t Sonny Burton novels., 2020)
"After Texas Ranger Sonny Burton loses his arm in a shootout with Bonnie and Clyde, he is asked by the Rangers to help find an escaped convict, Billy Bunson, who took a pregnant woman hostage. Once he begins his investigation, Sonny suspects there is more to Billy's plan than meets the eye. He suspects it's a plan for Billy to be free of Sonny once and for all. The story unfolds over a period of twenty-five years as Sonny Burton's life as a Texas Ranger intersects with Billy Bunson's life as a simple thief, who then transforms into a ruthless man killer. Sonny uses all of his skill as a lawman to track Billy down, where they face off for one last time"--